Potentially Inappropriate Medication Dispensing in Outpatients: Comparison of Different Measurement Approaches - Eggli Y; Halfon P; Zeukeng MJ; Kherad O; Schaller P; Raetzo MA; Klay MF; Favre BM; Schaller D; Marti J (Dove Medical Press, 2023)
Yves Eggli,1 Patricia Halfon,1 Minette-Joëlle Zeukeng,2 Omar Kherad,3 Philippe Schaller,2 Marc-André Raetzo,2 Michael Frédéric Klay,2 Benoît Marc Favre,2 Dorian Schaller,2 Joachim Marti1 1Centre for Primary Care and Public Health (Unisanté), University of Lausanne, Lausanne, Switzerland; 2Réseau Delta, Lancy, Switzerland; 3Internal Medicine Department, La Tour Hospital and University of Geneva, Geneva, SwitzerlandCorrespondence: Yves Eggli, Centre for Primary Care and Public Health (Unisanté), ECOSAN, Route de la Corniche 10, Lausanne, 1010, Switzerland, Tel +41 21 314 33 83, Email yves.eggli@unisante.chPurpose of the Research: This paper aims at comparing different approaches to measure potentially inappropriate medication (PIM) with routinely collected data on prescriptions, patient age institutionalization status (ie in nursing home or in the community). A secondary objective is to measure the rate and prevalence of PIM dispensing and to identify problematic practices in Switzerland.Material and Methods: The studied population includes about 90,000 insured over 17 years old from a Swiss health maintenance organization in 2019 and 2020. We computed and compared the number of PIM per patient for Beers criteria, Priscus list, Laroche, NORGEP and Prescrire approaches. We also created a composite indicator that accounts for the specificities of the Swiss context (adaptation to the Swiss drugs' market, recommendations in force related to sleeping pills, anxiolytics and NSAIDs). We also stratified the analysis per physician, including initiation and cessation of PIM prescription.Results: Our comparison revealed similarities between the approaches, but also that each of them had specific gaps that provides further motivation for the development of a composite approach. PIM rate was particularly high for sleeping pills, anxiolytics, NSAIDs, even when analyses were limited to chronic use. Drugs with anticholinergic effect were also frequently prescribed. Based on our composite indicator, 27% of insured over 64 years old received at least one PIM in 2020, and 8% received more than one. Our analyses also reveal that for sleeping pills and anxiolytics, half of the volume (or prevalence?) occurs in the < 65 population. We observed strong variations between physicians and a significant proportion of new users among patients with PIM.Conclusion: Our results show that PIMs prescribing is very frequent in Switzerland and is driven mostly by a few drug categories. There is important physician variation in PIM prescribing that warrants the development of intervention targeted at high PIM-prescribers.Keywords: low-value care, inappropriateness, medication, outpatients, Switzerland